Developing GUI and tools in Houdini software - Kou, Zhigang. (2013)
Houdini is popular 3D animation software for modeling and making visual effects and animation. Houdini has its procedural and node-based workflow to create simulations. It is now t convenient for artists especially beginners to create smoke and fire simulations within short time. It is also trick for beginners to effectively control their simulation. This project is to understand how Houdini creates fire simulations and discover how to improve the existing GUI. The project is also to create tools and develop GUI which can make it easier for artists to create smoke and fire simulations.